Writing in crooked lines: a dynamic analysis of writing development in neo-literate Bambara women - Davison, Cathy Joyce (University of the Free State, 2014)
Learning to write is not a linear process by which a student, whether child or adult, moves from strength to strength, first acquiring one skill then moving on to the next. It is rather a “crooked” path where different interacting factors move forward and backward, creating a pattern of development as writing skills emerge. This study investigates the developmental patterns involved in emergent writing skills of 20 previously illiterate Bambara women in Bamako, Mali. It examines the preliminary process of skills development in basic letter production as a precursor which may hinder or enhance the practice of writing as self-expression. Three developmental contexts unite to make this study on writing both informative and unique: adult basic literacy skills, an African language and early writing processes. Dynamic Systems Theory is employed as a means of analyzing a variable of interest consisting of letter formation, alignment, size and spacing as they reflect periods of stability and change over time in a non-linear, self-organizing, open system. The analysis leads to a proposed model of writing development in Bambara adults and the implications that such a model could have for understanding the process of writing acquisition by the adult learner. The study addresses questions regarding the presence of distinct patterns in writing skills development, whether such patterns are the same intra-individually and between adult and child learners, and the implications of patterning, in particular regression in patterning, for teaching and evaluation. Findings of the research indicate not one overall pattern for the study, but separate and distinct patterns in each learner. The patterns in the data of each individual are unique in respect to the range and percentage of output, the order of development of different sub-skills, and the progression and regression of each sub-skill. From the data, it is not possible to predict for a particular individual or to generalize for the population as a whole which factors will act in concert or in competition. The patterns evident in the data are not the same intra-individually. However, given the flexibility of patterns of development among individual learners, it may be said that the data in this study support the proposition that neo-literate adults in a non-literate context pass through the same stages of development in the writing process as do children. The concepts foundational to writing skills, including basic directionality and linearity of text, word spacing and letter formation, must still be given a chance to develop in each new adult writer. In a proposed model of emergent writing development, the elements which varied intra-individually were separated from the generalities that were consistent across the data. This consistency was evident in the types of patterns formed by the roles or functions expressed by each of the elements in the variable of interest. So while the data cannot indicate a particular order of development or interaction among the elements, they do indicate specific roles and functions that will be evident within the variable of interest at any given point. Study findings reinforce the following concepts: - regression in performance in one area may be a positive indicator of learning in another; - scaffolding and revision may lessen the cognitive load and enhance learning; - a balance between whole class and individualized instruction will respond to the needs of different learning patterns; - continuous, or at least frequent, assessment will create a more accurate learning profile; - the scope of assessment should include awareness of the various interacting elements in skills development.
Thesis(Ph.D.(Language Practice))--University of the Free State, 2014
Keywords: Adult literacy; Bambara; Dynamic systems; Instruction; Language development; Learning patterns; Learning process; Literacy; Women’s literacy; Writing